Criticism of the Sociocultural Theory - Maryam Ameri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Sociocultural theory is an emerging theory in psychology that looks at the important contributions that society makes to individual development. This theory stresses the interaction between developing people and the culture in which they live. Sociocultural theory also suggests that human learning is largely a social process. Psychology is one of the newest sciences. Over the years, social scientists have developed theories or perspectives based off of their observations, research, and the perspectives of other scientists. Although there is some overlap, each of the major perspectives of psychology is unique. As a result, they each have strengths and weaknesses and explain psychology in a different way. SLA research in the tradition of sociocultural theory examines the dynamic relationship between interaction and acquisition, exploring how language, cognition, and culture are acquired through collaborative interaction. This paper presents an analysis of The Strengths and Weaknesses of the Sociocultural Theory and to present a general overview of Sociocultural Theory (SCT), and its relation to human cognitive development.